Study on newly developed drill bit monitoring system for composite assembly in aerospace industry - Azhar, Nur Hafizah Kamal (Universiti Sains Malaysia, 2017)
Aerospace industry is the current multi- billionaire developed industry, where the demands for the air transportation has increasing significantly day by days as people nowadays required short time to travel from one place to another to do their business. Due to this reason, this industry needs reliable monitoring system to ensure aircraft can fly without facing the catastrophic failure. So, the monitoring system is used to maintain the performance of the aircraft manufacturing such as drilling process, which is one of the major machining processes in the Aerospace industry. The aim of a monitoring system for drilling process is to observe the drill wear pattern so it will not damage the workpieces in the next usage, as all products in Aerospace industry usually are the high- end product that cost a huge amount of money. Monitoring system can be used as one part of the inspection in the aerospace industry. Furthermore, this inspection process will use a digital microscope as the sensor to capture the images of the drill bit, meanwhile a computer program will be used for the inspection part. Then, the analysis will be made by using designed programming to calculate the value of the wear pattern. For this research, the study of the current manufacturing practices for drilling process in the aerospace industry by carry out case study. This research can help to test the performance and capability of the newly developed drill bit monitoring system in the Aerospace industry. Lastly, by having this research, the reliability of the newly developed monitoring system can be determined by looking at the results and suggestion, besides the suggestions will be made to improve the reliability of it.